2012
DOI: 10.1007/s00281-012-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted roles of PGE2 in inflammation and cancer

Abstract: Prostaglandin E2 (PGE2) is a bioactive lipid that elicits a wide range of biological effects associated with inflammation and cancer. PGE2 exerts diverse effects on cell proliferation, apoptosis, angiogenesis, inflammation and immune surveillance. This review concentrates primarily on gastrointestinal cancers, where the actions of PGE2 are most prominent, most likely due to the constant exposure to dietary and environmental insults and the intrinsic role of PGE2 in tissue homeostasis. A discussion of recent ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
377
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(399 citation statements)
references
References 144 publications
7
377
0
2
Order By: Relevance
“…Besides, PGE 2 induces activation and expansion of both Tregs and MDSC (myeloid-derived suppressor cells) and thus supports immunosuppression in cancer milieu. 60 Human MC express multiple PGE2 receptors EP(2–4) with major expression of EP2 and EP3. 61 EP2 and EP4 have been reported as inhibitory receptors for MC activation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PGE 2 induces activation and expansion of both Tregs and MDSC (myeloid-derived suppressor cells) and thus supports immunosuppression in cancer milieu. 60 Human MC express multiple PGE2 receptors EP(2–4) with major expression of EP2 and EP3. 61 EP2 and EP4 have been reported as inhibitory receptors for MC activation.…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 is the most common PG derived from COX2 (Nakanishi & Rosenberg 2013). To determine whether EGF-induced COX2 expression contributes to the production of PGE2, we measured PGE2 protein levels in the culture medium by ELISA after 1, 3, and 6 h of EGF treatment.…”
Section: Cox2 and Pge2 Mediate Egf-induced Cell Invasionmentioning
confidence: 99%
“…PGE2 is an important PG that acts in an autocrine/paracrine manner to regulate various physiological and pathological functions (Nakanishi & Rosenberg 2013). Two isoforms of COX, COX1 and COX2, have been described.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies have shown that PGE 2 promotes tumor development by enhancing cell proliferation and survival, inflammation, angiogenesis, and invasiveness in various cancers. [4][5] The PGE 2 receptors EP1 and EP2 have been demonstrated to participate in PGE 2 -induced tumorigenesis as well as in PGE 2 -mediated cancer cell survival and protection from druginduced apoptosis, via the activation of cyclic adenosine monophosphate (cAMP)-dependent protein kinase A (PKA). 6,7 PGE 2 has been shown to significantly increase promonocytic cell proliferation and COX-2 expression, and this effect is mediated, at least in part, by the activation of the Ras/Raf/Erk signaling cascade.…”
Section: Introductionmentioning
confidence: 99%